Original paperTHE EFFECT OF N-3 LC-PUFA SUPPLEMENTATION ON TENNIS SKILL ACQUISITION IN 10-12 YEAR OLD GIRLS - Seferoğlu, F.; Erman, A.; Şahan, A.; Toktaş, N. (Biology of Sport, 2012)
The purpose of this study was to investigate the effects of 16 weeks of n-3 LC-PUFA (omega 3 long-chain polyunsaturated fatty acid) supplementation on tennis skill acquisition in 10-12 year old girls. This research was a single-blind placebo-controlled trial. 29 girls (10-12 years of age) who had never played tennis before took part in the study. Ball Throws to the Target (BTT) and Tennis Ability Test (TAT) were performed three times. Before participants were allocated to the groups and received n-3 LC-PUFA or olive oil, they underwent preparatory training for three weeks. Anthropometric measurements, nutrition analysis, and 1st BTT and TAT tests were performed and they continued the preparatory training until the 3rd week. Then they were randomly allocated to two groups to receive either n-3 LC-PUFA (omega group; 670 mg · day-1; n=16) or olive oil (placebo group; 670 mg · day-1; n=13) during 16 weeks of tennis training which involved 3 hours per week for 19 weeks. The results show that significant improvements in TAT were found in both groups but the omega group had significantly higher scores than the placebo group at the 3rd measurements. Although there were no differences between groups at all measurements of BTT, the omega group showed significant improvement between the 1st and 3rd measurements. This study suggests that daily 670 mg n-3 LC-PUFA supplementation for 16 weeks might improve tennis ability test scores of 10-12 year old girls.